Analysis of Business Efficiency Level of Beef Cattle in Banggai District of Central Sulawesi - Supardi Rusdiana; Soeharsono Soeharsono (Buletin Peternakan, 2018)
This study aims to determine the level of efficiency analysis of beef cattle business in breeders. The research was conducted in Batui Sub-district, Banggai Regency, Central Sulawesi in 2015, using completely randomized design (CRD), with control I, treatment II = 1 + supplemented feed 1.00% of body weight, treatment III = 1 + supplement feed 1,50% of body weight and treatment IV = 1 + supplemented feed 2.00% of body weight, according to the weight of the livestock. Primary data obtained from interviews on business units of beef cattle farmers, while secondary data obtained from the relevant agencies. The collected data were analyzed descriptively, qualitatively and economic analysis. The results showed that income on the implementation of supplemented feed of the highest concentrate feed was achieved at 2.00% supplementation level. The gain in control I is IDR13,680,-/head, R/C ratio 1.50 and B/C ratio 0.56, treatment II IDR19,380,-/head, R/C 2.15 and B/C 1.15, treatment III of IDR25,080,-/head, R/C ratio 2.26 and B/C ratio 1.26 and treatment IV of IDR28,500,-/head, R/C 2.44 and B/C 1.44. Financially, beef cattle business is profitable and shows the feasibility of cattle business deserve to be developed.